Moment matching for nonlinear differential-algebraic equations - Scarciotti,G (IEEE, 2016)
The problem of model reduction by momentmatching for nonlinear singular systems is considered. Thenotion of moment is extended to this class of systems bymeans of the center manifold theory. The characterization ofthe moments at infinity and of the moments for nonlinearparametric singular systems is discussed. The problem of modelreduction for singular perturbation systems is analyzed. Afamily of singular reduced order models achieving momentmatching is presented. Throughout the paper the results areillustrated by means of examples.